2020
DOI: 10.1530/edm-20-0110
|View full text |Cite
|
Sign up to set email alerts
|

Successful remission of type B insulin resistance syndrome without rituximab in an elderly male

Abstract: Summary Type B insulin resistance syndrome (TBIR) is a rare autoimmune disease caused by antibodies against the insulin receptor. It should be considered in patients with dysglycaemia and severe insulin resistance when other more common causes have been ruled out. We report a case of a 72-year-old male with a 4-year history of type 2 diabetes who presented with hypercatabolism, vitiligo, acanthosis nigricans, and hyperglycaemia resistant to massive doses of insulin (up to 1000 U/day). Detection of anti-insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It should be noted that most patients do not meet all the criteria for a specific autoimmune disease. 6 Occasionally, patients develop initial or secondary hypoglycemia, in some cases with unsuppressed insulin, which could be due to defective degradation of insulin–insulin receptor complexes. 9 Although the treatment is mainly done empirically, several case reports suggested therapeutic benefits of different agents, including cyclophosphamide, corticosteroids, azathioprine, rituximab, and plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that most patients do not meet all the criteria for a specific autoimmune disease. 6 Occasionally, patients develop initial or secondary hypoglycemia, in some cases with unsuppressed insulin, which could be due to defective degradation of insulin–insulin receptor complexes. 9 Although the treatment is mainly done empirically, several case reports suggested therapeutic benefits of different agents, including cyclophosphamide, corticosteroids, azathioprine, rituximab, and plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although the treatment is mainly done empirically, several case reports suggested therapeutic benefits of different agents, including cyclophosphamide, corticosteroids, azathioprine, rituximab, and plasmapheresis. [3][4][5][6][7] However, combination immunosuppressive therapy is also reported in this regard. In a prospective cohort study, 22 patients with confirmed TBIRS were administered combination of rituximab, cyclophosphamide and high-dose pulsed steroids until remission (defined as hyperglycemia amelioration and insulin discontinuation and/or hyperandrogenemia normalization) followed by maintenance therapy with azathioprine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations